2003
DOI: 10.1021/ja026917a
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Cross-Linking Approach for Exploring Protein Interactions

Abstract: A method is described for the elucidation of protein-protein interactions using novel cross-linking reagents and mass spectrometry. The method incorporates (1) a modular solid-phase synthetic strategy for generating the cross-linking reagents, (2) enrichment and digestion of cross-linked proteins using microconcentrators, (3) mass spectrometric analysis of cross-linked peptides, and (4) comprehensive computational analysis of the cross-linking data. This integrated approach has been applied to the study of cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
168
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(174 citation statements)
references
References 24 publications
0
168
0
5
Order By: Relevance
“…In order to increase the yield of high quality assignments of cross-linked peptides, they will need to be purified directly. There have been suggestions for enrichment strategies based on affinity tagged cross-linkers, which, however, are not available in isotopically coded form yet or have isotopic signatures too small for electrospray ionization 14,15 . Having shown that high throughput identification of cross-linked peptides is now feasible it should spark interest to invest in advanced enrichment strategies for crosslinked peptides.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the yield of high quality assignments of cross-linked peptides, they will need to be purified directly. There have been suggestions for enrichment strategies based on affinity tagged cross-linkers, which, however, are not available in isotopically coded form yet or have isotopic signatures too small for electrospray ionization 14,15 . Having shown that high throughput identification of cross-linked peptides is now feasible it should spark interest to invest in advanced enrichment strategies for crosslinked peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to multiple major technical obstacles it had been impossible until recently to directly and reliably identify crosslinked peptides from protein complexes by MS (see [1][2][3][4] for recent reviews). After early work on individual proteins [5][6][7] and protein complexes [8,9], notably by the Sinz and Rappsilber groups, Aebersold and coworkers introduced the first robust general workflow by optimizing wet-lab protocols and the development of the publicly available xQuest/xProphet open-source software suite for the analysis and validation of crosslinks from large protein complexes by MS [10][11][12].Over the past few years the field has seen significant progress and several methods to enrich crosslinks [13][14][15], various crosslinking chemistries [9,10,[15][16][17][18][19][20][21][22], and the introduction of multiple detection and identification strategies [9][10][11][23][24][25][26][27][28]. Statistical models that differentiate true from false identifications have also been developed [10].…”
mentioning
confidence: 99%
“…Other biotinylated crosslinkers could be synthesized to accommodate a wider variety of proteins and protein complexes. A biotinylated homobifunctional crosslinker with two NHS groups, both reactive toward primary amines on proteins [21], is one such possibility; such a reagent would reduce the non-specificity introduced by the arylazide group of sulfo-SBED. Preliminary evidence suggests that tandem mass spectrometry experiments, such as MS-MS or MS 3 , can identify the two peptides in a crosslinked pair [5,10,28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a separation method for enriching the analyte mixture in the crosslinked species would be useful for reducing levels of non-crosslinked peptides while simultaneously increasing the concentration of crosslinked species in the analyte mixture. An affinity separation provides such an advantage, as demonstrated by Trester-Zedlitz et al [21]. The biotin-avidin interaction is a logical choice for this affinity separation; a biotin-labeled crosslinker can be extracted, along with its attached peptide(s), from a complex peptide mixture using an immobilized avidin separation medium.…”
mentioning
confidence: 99%